VD_FINDINFO HC / 2021 / 761 vom 7. Oktober 2021 - VD Tribunal cantonal (2021)
ENFANT, OBLIGATION D'ENTRETIEN, GARDE ALTERNÉE, DOMICILE, CONTRIBUTION DE PRISE EN CHARGE | 25 al. 1 CC, 285 al. 1 CC, 285 al. 2 CC